(untitled) (ouvirOUver, 2015)
Esta pesquisa tem como objetivo analisar as relações da quadrícula desde o seu surgimento, na pintura renascentista, na quadratura na arte barroca, da grade na arte contemporânea, e por fim sua permanência enquanto elemento constitutivo das imagens digitais através do pixel. Nesse sentido, a imagem é entendida numa linha evolutiva: a quadrícula e a quadratura enquanto soluções pictóricas para o domínio do realismo e do ilusionismo na renascença e no barroco, sua permanência na arte contemporânea enquanto elemento de construção/desconstrução culminando na apropriação destas soluções como sintaxe das imagens tecnológicas através do pixel. ABSTRACT This research aims to analyze the relations of the grid since its emergence in Renaissance painting, quadratura in Baroque art, the square grid in contemporary art, and finally, their permanence as a constituent of digital images through the pixel. In this sense, the image is understood as an evolutionary line: a square grid and the quadratura as pictorial solutions for the domain of realism and illusionism in Renaissance and Baroque, their permanence in contemporary art as part of construction /deconstruction culminating in the appropriation of these solutions as technological image syntax through the pixel. KEYWORDS Square grid, quadratura, pixel.